1989
DOI: 10.1152/ajpregu.1989.256.6.r1348
|View full text |Cite
|
Sign up to set email alerts
|

Fetal responses to long-term hypoxemia in sheep

Abstract: The effect of acute or short-term hypoxia on fetal cardiovascular hemodynamics has been well known; however, little is known about the effect of long-term hypoxemia. To determine the fetal hemodynamic responses to this stress we studied two groups of animals: 1) pregnant ewes (n = 20) at 110-115 days of gestation subjected to hypoxia for up to 28 days and 2) pregnant ewes (n = 4) that served as normoxic controls. We chronically catheterized the fetal brachiocephalic artery and vein. Five to 6 days after surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
66
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 0 publications
13
66
0
1
Order By: Relevance
“…Kitanaka et al (23) showed that fetuses exposed to 28 days of hypoxemia via high altitude responded by increasing their hemoglobin and hematocrit over time to normalize arterial oxygen contents; these fetuses grew at normal rates, indicative of normal fetal nutrient metabolism. In contrast, our model allowed us to chronically match the mean oxygen content of PI-IUGR fetuses (2.0 mmol/l) (7,28,47).…”
Section: Discussionmentioning
confidence: 99%
“…Kitanaka et al (23) showed that fetuses exposed to 28 days of hypoxemia via high altitude responded by increasing their hemoglobin and hematocrit over time to normalize arterial oxygen contents; these fetuses grew at normal rates, indicative of normal fetal nutrient metabolism. In contrast, our model allowed us to chronically match the mean oxygen content of PI-IUGR fetuses (2.0 mmol/l) (7,28,47).…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced blood pressure observed in the preexisting hypoxia during the last two days of the five-day hypoxia period most likely reflects an increase in circulating catecholamines (Kitanaka et al, 1989). An elevation in plasma catecholamines elicited by chemoreceptor mechanisms is also thought to be responsible for the initial hypertension (Boekkooi et al, 1992;Cohn et al, 1974;Giussani et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…There was no effect of either periconceptional or gestational undernutrition on fetal heart rate or on the decrease in fetal heart rate that occurs with increasing gestational age (16,37). The rpp (rpp ϭ systolic BP ϫ heart rate) has been used as a marker of myocardial oxygen consumption and thus of cardiac work in the sheep fetus (14) and human adult (15,29).…”
Section: Discussionmentioning
confidence: 99%